Mechanistic investigation of human maturation of Okazaki fragments reveals slow kinetics - Raducanu, Vlad-Stefan; Tehseen, Muhammad; Al-Amodi, Amani; Joudeh, Luay I.; De Biasio, Alfredo; Hamdan, Samir M. (Nature communications, 2022)
The final steps of lagging strand synthesis induce maturation of Okazaki fragments via removal of the RNA primers and ligation. Iterative cycles between Polymerase δ (Polδ) and Flap endonuclease-1 (FEN1) remove the primer, with an intermediary nick structure generated for each cycle. Here, we show that human Polδ is inefficient in releasing the nick product from FEN1, resulting in non-processive and remarkably slow RNA removal. Ligase 1 (Lig1) can release the nick from FEN1 and actively drive the reaction toward ligation. These mechanisms are coordinated by PCNA, which encircles DNA, and dynamically recruits Polδ, FEN1, and Lig1 to compete for their substrates. Our findings call for investigating additional pathways that may accelerate RNA removal in human cells, such as RNA pre-removal by RNase Hs, which, as demonstrated herein, enhances the maturation rate ~10-fold. They also suggest that FEN1 may attenuate the various activities of Polδ during DNA repair and recombination. Here, the authors investigate the maturation of Okazaki fragments with human proteins and reveal that initiator RNA removal occurs non-processively and slowly suggesting that additional pathways might exist to accelerate RNA removal in cells.